2017
DOI: 10.1080/1028415x.2017.1418726
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect ofCamellia sinensisteas on object recognition test deficit and metabolic changes induced by cafeteria diet

Abstract: According to the results obtained it is possible to conclude that green tea was better than other teas in reducing effects of the CD model, being able to protect a greater number of parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Hereafter, we present a model of cafeteria diet with palatable foods which are largely consumed by humans, and it is very palatable to rodents. This cafeteria diet model have been homogenized for a greater standardization and was used in few experiments in the literature, but the liver of the animals was not evaluated (Estadella et al, 2011;Schimidt et al, 2018;Rocha-Gomes et al, 2019;Soares et al, 2019;Teixeira et al, 2020). The aim of the present study was to evaluate the liver tissue of adult Wistar rats treated from birth to adulthood with cafeteria diet considering the biochemical, histopathological and redox state parameters of this organ.…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter, we present a model of cafeteria diet with palatable foods which are largely consumed by humans, and it is very palatable to rodents. This cafeteria diet model have been homogenized for a greater standardization and was used in few experiments in the literature, but the liver of the animals was not evaluated (Estadella et al, 2011;Schimidt et al, 2018;Rocha-Gomes et al, 2019;Soares et al, 2019;Teixeira et al, 2020). The aim of the present study was to evaluate the liver tissue of adult Wistar rats treated from birth to adulthood with cafeteria diet considering the biochemical, histopathological and redox state parameters of this organ.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown a significant increase in AChE activity in neurodegenerative diseases such as AD [ 202 ]. This increase may be related to abnormal neurotransmitter metabolism and disturbances in cholesterol homeostasis [ [203] , [204] , [205] ]. Disruption of cholesterol homeostasis may lead to abnormal changes in cell membranes, affecting neurotransmission [ 206 , 207 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effect of the high-fat diet has been demonstrated in the study by Gonçalves et al (2017), in which the descendants of mothers who received a highfat diet had a reduction in the global levels of histone acetylation in the hippocampus of male offspring in adulthood, is linked to gene silencing related to brain function. Soares et al (2017), showed that cafeteria diet consumption in mices caused weight gain, body fat accumulation, increased glucose, cholesterol, and triglycerides, associated to recognition memory deficits and increased reactive species (RS) levels and acetylcholinesterase (AChE) activity in the hippocampus. However, white, green, red and black (Camellia sinensis) significantly reduced these levels, showing benefits.…”
Section: Discussionmentioning
confidence: 99%